Addressing Gender-Based Violence in Latin America and the Caribbean : A Critical Review of Interventions - Morrison, Andrew; Ellsberg, Mary; Bott, Sarah (World Bank, Washington, DC, 2012)
The authors present an overview of gender-based violence (GBV) in Latin America, with special emphasis on good practice interventions to prevent GBV or offer services to its survivors or perpetrators. Intimate partner violence and sexual coercion are the most common forms of GBV and these are the types of GBV that they analyzes. GBV has serious consequences for women's health and well-being, ranging from fatal outcomes, such as homicide, suicide and AIDS-related deaths, to non-fatal outcomes, such as physical injuries, chronic pain syndrome, gastrointestinal disorders, complications during pregnancy, miscarriage, and low birth-weight of children.